2014
DOI: 10.3109/02713683.2013.853195
|View full text |Cite
|
Sign up to set email alerts
|

Acute Exposure of Rabbit Eyes to Artificial Lightin Vivo: Effect on Corneal and Third Eyelid Conjunctival Histology and the Gene Expression of PAFR

Abstract: Acute exposure of rabbit eyes to artificial sunlight induced a marked infiltration of eosinophils into the epithelial layer of the conjunctiva but no gross alterations in the cornea or the third eyelid. The gene expression of PAFR was upregulated, as an effect of light exposure, in the third eyelid but not in the cornea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The nictitating membrane can extend over the cornea as a result of the whole eye retracting into the bony orbital cavity surrounding the eye . As such, a nictitating membrane response can occur when there is exposure to high doses of UV‐R, a response that could serve to protect the cornea . It is therefore important to note that if the eyelids are held open during experimental UV‐B exposure of rabbit eyes, there can be no protective response (see the section discussing the preparation of rabbits for UV‐R exposure).…”
Section: In Vivo Observational Assessments Of the Rabbit Cornea Beformentioning
confidence: 99%
See 1 more Smart Citation
“…The nictitating membrane can extend over the cornea as a result of the whole eye retracting into the bony orbital cavity surrounding the eye . As such, a nictitating membrane response can occur when there is exposure to high doses of UV‐R, a response that could serve to protect the cornea . It is therefore important to note that if the eyelids are held open during experimental UV‐B exposure of rabbit eyes, there can be no protective response (see the section discussing the preparation of rabbits for UV‐R exposure).…”
Section: In Vivo Observational Assessments Of the Rabbit Cornea Beformentioning
confidence: 99%
“…Following exposure to very high doses of UV‐B, it has also been reported that new blood vessels can form and grow into the peripheral cornea , a process that may be referred to as neovascularization . The nictitating membrane is also covered with conjunctival cells and these can be adversely affected by UV‐R exposure .…”
Section: In Vivo Observational Assessments Of the Rabbit Cornea Beformentioning
confidence: 99%
“…Physiological differences based on species may therefore impact the applicability of using animal responses to predict the human response. For example, the presence of the nictitating membrane, an inner, translucent membrane that can extend and retract over the corneal surface in the rabbit, may influence the corneal response to stimuli (Varsamidou et al, 2014) compared to the human, which lacks this structural feature. Interspecies variability is also exemplified by relative differences in corneal thickness with the bovine cornea having one of the thickest corneas (800-1000 μm) of animal models (Doughty, 2000).…”
Section: Challenges With Current Approaches To Predict Ocular Discomfortmentioning
confidence: 99%